Three-Dimensionally Printed Vaginal Rings: Perceptions of Women and Gynecologists in a Cross-Sectional Survey - Laura Andrade Junqueira; Francisco José Raposo; Geraldo Sérgio Farinazzo Vitral; Atabak Ghanizadeh Tabriz; Dennis Douroumis; Nádia Rezende Barbosa Raposo; Marcos Antônio Fernandes Brandão (MDPI AG, 2023)
Three-dimensional printing technologies can be implemented for the fabrication of personalized vaginal rings (VRs) as an alternative approach to traditional manufacturing. Although several studies have demonstrated the potential of additive manufacturing, there is a lack of knowledge concerning the opinions of patients and clinicians. This study aimed to investigate the perception of women and gynecologists regarding VRs with personalized shapes. The devices were printed with different designs (traditional, "Y", "M", and flat circle) by Fused Deposition Modeling for a cross-sectional survey with 155 participants. Their anticipated opinion was assessed through a questionnaire after a visual/tactile analysis of the VRs. The findings revealed that most women would feel comfortable using some of the 3D-printed VR designs and demonstrated good acceptability for the traditional and two innovative designs. However, women presented multiple preferences when the actual geometry was assessed, which directly related to their age, previous use of the vaginal route, and perception of comfort. In turn, gynecologists favored prescribing traditional and flat circle designs. Overall, although there was a difference in the perception between women and gynecologists, they had a positive opinion of the 3D-printed VRs. Finally, the personalized VRs could lead to an increase in therapeutic adherence, by meeting women's preferences.